How Is The Implementation of Social Media Marketing In The Hospital Industry? - Nanda Annisa Rahmawati; Warih Kusumaningtyas; Eka Rosina Korelia (Jurnal Indonesia Sosial Teknologi, 2024)
The hospital industry with a variety of increasingly strict government rules and increasing hospital choices creates tough competition. The purpose of this study is to find out how is the implementation of social media marketing in the hospital industry?. In private hospitals, a good marketing strategy is needed to continue to increase public trust. In the era of marketing 5.0 (technology with humanity) requires hospitals to continue to innovate in terms of services and technology. Social media marketing is one way to image the hospital in the eyes of the public. Marketing using social media has low capital and is easy to do. Delta Surya Hospital is one of the type C private hospitals in Sidoarjo that has applied the principles of social media marketing. The data was taken in November 2022 by analyzing the hospital's social media, namely Instagram, YouTube, and TikTok. The results of the data were compared with similar journals that already existed.